Quo Vadis "Living Human Treasures"? - Nicolae Lupu; Mihail Ovidiu Tănase; Petronela Tudorache (Amfiteatru Economic Journal, 2016)
"Living Human Treasures" (LHT) is a program supported by the United Nations Educational, Scientific and Cultural Organization (UNESCO). According to the Regulation of the Ministry of Culture in Bucharest, the title "Living Human Treasures" is the life contingency, personal and in transmissible. The person "must, simultaneously fulfill bearing, preserving and creating qualities of intangible heritage, be able to transmit traditional cultural models and be recognized as so by other LHT and the scientific community". In six years, between 2010 and 2015 in Romania were granted 45 titles: half to craftsmen (weavers, carpenters, iconographers, furriers, builders of musical instruments, pottery etc.) and half to performers of folklore (folk interpreter, rhapsodists, dancers etc.). Most distinctions, eight and seven, were awarded in Cluj and Alba county, followed by Bra?ov, Suceava county, each with five distinctions. Discussions are held about the possibilities of granting life annuity, following the model of athletes and some artists and writers. It is clear however that the title holders and their performance can be assimilated to tourism assets, as attractions of itself, transforming communities they belong to genuine tourist destinations. Furthermore, it would avoid the exhausting movements of artisans at the various trade fairs, being preferable to receive the audience in their personal household tranquility. A series of semi structured personal interviews with some LHT confirm this hypothesis. Strong promotion of those tourist destinations should no longer delay. At the central level it would require that the Tourism Authority take the "dossiers" for those LHT and promote them in a centralized manner, dedicating them an advertising brochure and a map.
Keywords: Z13; Z32; 330; Living Human Treasure; keepers and transmitters of traditions; immaterial heritage; anthropogenic tourism potential